Hahnemann's Achievements and Modern Medicine - Morrell, Peter (Homœopathic Links, 2016)
This essay gives a brief outline of Hahnemann's energy, achievements and publications with a brief comparison of homeopathy to modern medicine.
Keywords: Hahnemann; energy; achievements; allopathy; palliation